In search of the interrelatedness of innovation and internationalisation processes in entrepreneurial life science companies - Rilla, Nina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study is motivated by the question how resource scarce innovative entrepreneurial companies seek and leverage global resources. This study takes a resource-seeking perspective a step forward and suggests that resources that enable the entrepreneurial internationalisation are largely accrued from the early stages of entrepreneurial life; that is from the innovation development. Consequently, this study seeks to explain how innovation and internationalisation processes are interrelated in the entrepreneurial internationalisation. This main objective is approached through three research questions, (1) What role do inter-organisational relationships in innovation have in the entrepreneurial internationalisation process? (2) What kind of inward–outward links do inter-organisational relationships create in the resource-seeking-based entrepreneurial internationalisation process? (3) What kind of capability to collaborate forms in the interaction of inter-organisational relationship deployment? The research design is a mixed methods design that consists of quantitative pilot study and qualitative multiple case study of five entrepreneurial life science companies from Finland and Austria. The findings show that innovation and internationalisation processes are tightly interwoven in pre-internationalisation state. The findings also reveal that the more experienced companies are able to take advantage of complexcross-border inter-organisational relationship structures better than the starting companies. However, very minor evidence was found on inward links translating into outward links in the entrepreneurial internationalisation process, despite the expectation to observe more of these links in the data. Combined intangible-tangible resource-seeking was the most preferred to build links between inward–outward internationalisation but also to develop competence to collaborate. By adopting a resource- instead of market-seeking approach, this study illustrated that internationalisation extends to early stages of innovative companies, and that in high-technology companies’ potentially significant cross-border relationships have started to form long before incorporation. Therefore, these observations justified the firmer inclusion of pre-company history in innovative entrepreneurship studies. The study offers a conceptualisation of entrepreneurial internationalisation that is perceived as a process. The main theoretical contributions are in the areas of international entrepreneurship and in the behavioural process studies of entrepreneurial internationalisation and resource-based internationalisation. The inclusion of the innovation-based discussion, namely the innovation process, in the internationalisation process theories has clearly contributed to the understanding of entrepreneurial internationalisation in the context of international entrepreneurship. Innovation development is a central act of entrepreneurial companies, and neglecting innovation process investigation from entrepreneurial internationalisation leaves potentially influential mechanisms unexplored.

Yrittäjävetoisten life science -yritysten innovaatio- ja kansainvälistymisprosessien yhteyttä etsimässä Tämän tutkimuksen lähtökohtana on kysymys siitä, kuinka resurssiniukat innovatiiviset yrittäjävetoiset yritykset hakevat ja hyödyntävät globaalisti saa-tavilla olevia resursseja. Tutkimus laajentaa resurssien hankinta -näkökulmaa ja esittää, että yrittäjyysvetoisessa kansainvälistymisessä hyödylliset resurssit kertyvät enimmäkseen jo yrittäjyyden alkuvaiheessa eli innovaation kehittämisen aloittamisesta. Tämän vuoksi tutkimus pyrkii selittämään, kuinka innovaatio- ja kansainvälistymisprosessi ovat yhteydessä toisiinsa yrittäjyysvetoisessa kansainvälistymisessä. Tutkimuksen päätavoitetta lähestytään kolmen tutkimuskysymyksen kautta: (1) Minkälainen rooli organisaatioiden välisillä innovaatiosuhteilla on yrittäjyysvetoisessa kansainvälistymisprosessissa? (2) Minkälaisia sisäisiä ja ulkoisia linkkejä organisaatioiden väliset suhteet luovat resurssienhankkimisperustaiseen, yrittäjyysvetoiseen kansainvälistymisprosessiin? (3) Minkälainen yhteistyökyvykkyys muodostuu organisaatioiden välisten suhteiden hyödyntämisen vuorovaikutuksessa? Tutkimusasetelmana on monimenetelmätutkimus (mixed methods), joka koostuu määrällisestä pilotti-tutkimuksesta ja laadullisesta monitapaustutkimuksesta, jossa kohteena on viisi yrittäjävetoista life science -yritystä Suomesta ja Itävallasta. Tulokset osoittavat, että innovaatio- ja kansainvälistymisprosessi ovat tiukasti kietoutuneita toisiinsa yrityksen esikansainvälistymisasteesta alkaen. Lisäksi tutkimuksen havainnot paljastavat kokeneempien yritysten olevan valmiimpia hyödyntämään ulkomaisia monitahoisia yhteistyösuhteitaaloittavia yrityksiä paremmin. Ennakoidusta huolimatta yrittäjyysvetoisen kansainvälistymisprosessin sisäänpäin suuntautuvien linkkien muuntamisesta ulkoisiksi linkeiksi saatiin vain vähän todisteita. Kansainvälistymisen sisäistenja ulkoisten linkkien muodostumiseen vaikuttivat eniten resurssit, joissa yhdistyvät aineettomat ja aineelliset ulottuvuudet. Nämä samat resurssityypit olivat myös arvokkaita yhteistyökyvykkyyden muodostumisessa. Markkinoiden hankinta -näkökulman sijaan valittu resurssien hankinta -näkökulma paljastaa, että kansainvälistyminen ulottuu innovatiivisten yritysten ensivaiheisiin asti sekä sen, että korkean teknologian yrityksissä mahdollisesti merkittävät ulkomaiset yhteistyösuhteet ovat alkaneet muodostua kauan ennen yrityksen virallista perustamista. Nämä havainnot osoittavat tärkeäksi yrityksen esihistorian tiukemman sisällyttämisen innovatiivista yrittäjyyttä käsitteleviin tutkimuksiin. Tutkimus käsitteellistää yrittäjyysvetoisen kansainvälistymisen prosessiksi. Tutkimuksen kontribuutio kansainvälisen liiketoiminnan tutkimusalueella kohdistuu kansainväliseen yrittäjyyteen ja nimenomaan käyttäytymis- ja resurssiperustaisten prosessien ymmärtämiseen yrittäjyysvetoisessa kansainvälistymisessä. Innovaatioprosessin kytkeminen kansainvälistymisprosessiteorioiden tarkasteluun auttoi ymmärtämään yrittäjyysvetoista kansainvälistymistä innovaation kehityksen alkuajoista asti. Innovaation kehitys on keskeinentapahtuma yrittäjävetoisessa yrityksessä, ja innovaatioprosessin poissulkeminen kansainvälistymisen tarkastelusta saattaa jättää keskeisiä kansainvälistymisen mekanismeja kartoittamatta.